2021
DOI: 10.1093/ntr/ntab124
|View full text |Cite
|
Sign up to set email alerts
|

Multiethnic Prediction of Nicotine Biomarkers and Association With Nicotine Dependence

Abstract: Introduction The nicotine metabolite ratio and nicotine equivalents are measures of metabolism rate and intake. Genome-wide prediction of these nicotine biomarkers in multiethnic samples will enable tobacco-related biomarker, behavioral, and exposure research in studies without measured biomarkers. Aims and Methods We screened genetic variants genome-wide using marginal scans and applied statistical learning algorithms on top… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Confirmation of the African American TRHD of reduced abstinence using both the social construct of race and genomic ancestry, and the novel association of the predicted uNMR with abstinence, supports future analyses of cessation trials of sufficient sample size to observe and dissect disparities by ancestry 45 , models of nicotine metabolism and consumption 25,46 , socioeconomic factors 6 , and treatments. Such combined biopsychosocial cessation research would support reenvisioning of interventions in the context of the public health crises in the United States 47 .…”
Section: Translational Implicationsmentioning
confidence: 56%
“…Confirmation of the African American TRHD of reduced abstinence using both the social construct of race and genomic ancestry, and the novel association of the predicted uNMR with abstinence, supports future analyses of cessation trials of sufficient sample size to observe and dissect disparities by ancestry 45 , models of nicotine metabolism and consumption 25,46 , socioeconomic factors 6 , and treatments. Such combined biopsychosocial cessation research would support reenvisioning of interventions in the context of the public health crises in the United States 47 .…”
Section: Translational Implicationsmentioning
confidence: 56%
“…Muhammad‐Kah et al, found weak to moderate associations between urinary TNE in 24 h urines and nicotine dependence scores 38 . Bergen et al, reported correlations between urinary NMR and TNE with FTND score in the Multiethnic Cohort Study 39 . Overmeire et al found correlations between urinary levels of nicotine, cotinine, and 3HC with FTND score, especially with time before the first cigarette after waking 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine-N′-oxide formation accounts for 3%-5% of total urinary nicotine metabolites in humans. [33][34][35][36][37][38][39][40][41][42][43] Nicotine is oxidized to nicotine-N′-oxide by FMO1, FMO2, and FMO3, 44 which are expressed both hepatically and in extrahepatic tissues including brain. 45 In rats, nicotine N′-oxide has been found to be the second most abundant nicotine metabolite in blood and brain.…”
Section: Bergen Et Al Reported Correlations Between Urinary Nmr and Tnementioning
confidence: 99%
“…GWAS analyses included age, sex, BMI, principal components of genetic variation, genomic control values or relatedness matrices in GWAS analyses, and then performed inverse variance meta-analyses. NMR prediction models have selected variants from GWAS analysis [ 109 , 115 118 ], CYP2A6 pharmacogenetic alleles [ 116 , 117 ], and used weights from GWAS regression [ 109 , 116 , 117 ] and penalized regression and/or machine learning analyses for prediction [ 115 , 118 ]. Genomic NMR models have been externally validated with measured NMR values [ 116 118 ], smoking related behavior [ 109 , 115 ], and abstinence [ 116 , 117 ].…”
Section: Challenges and Opportunities For The Translation Of Biomarke...mentioning
confidence: 99%